Prairie establishment at the Field Station - (:unkn) unknown (My University, 1973)
Early in the development of the Cedar-Sauk Field Station it was decided to attempt establishing a sample of prairie vegetation as an experimental and demonstration project. Although none of the field station land had prairie soil and the nearest site of original native prairie was probably at least twenty miles distant, we felt that this area was close enough to the original prairies climatically so that most of the prairie species native to southeastern Wisconsin should be able to survive. If even moderately successful, it would provide an additional habitat for studies of animal life at the station, a demonstration area and species collection convenient for educational use, a gene pool for prairie plan ts for the future, and a test of direct seeding methods and treatments for prairie re-establishment.
Keywords: prairie establishment; UWM Field Station